2011
DOI: 10.1186/1556-276x-6-321
|View full text |Cite
|
Sign up to set email alerts
|

Porous silicon nanoparticles for cancer photothermotherapy

Abstract: The in vitro cell tests and in vivo animal tests were performed to investigate the feasibility of the photothermal therapy based on porous silicon (PSi) in combination with near-infrared (NIR) laser. According to the Annexin V- fluorescein isothiocyanate Apoptosis assay test results, the untreated cells and the cells exposed to NIR laser without PSi treatment had a cell viability of 95.6 and 91.3%, respectively. Likewise, the cells treated with PSi but not with NIR irradiation also had a cell viability of 74.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 45 publications
3
44
0
Order By: Relevance
“…A solid-state NIR laser (Ocean Optics), which emits light, (785 nm, 500 mW) was guided through an optical fiber the end of which was placed at 2 cm over the liquid/air interface. The temperature was measured using a TES 1326S/1327K infrared thermometer after irradiation pulses (Hong et al 2011;Fu et al 2012).…”
Section: Synthesis and Characterization Of Pani-npsmentioning
confidence: 99%
“…A solid-state NIR laser (Ocean Optics), which emits light, (785 nm, 500 mW) was guided through an optical fiber the end of which was placed at 2 cm over the liquid/air interface. The temperature was measured using a TES 1326S/1327K infrared thermometer after irradiation pulses (Hong et al 2011;Fu et al 2012).…”
Section: Synthesis and Characterization Of Pani-npsmentioning
confidence: 99%
“…Nanomedicines offer unprecedented advantages in targeted drug delivery into tumours, such as enhanced cellular uptake, controlled release of drugs, and protection of the agents from premature degradation 16 . A range of nanoparticles (NP) have been developed to deliver small molecular drugs to inhibit cancer cell migration [17][18][19] . Interestingly, a few studies reported that NP treatments alone are inhibitory to cancer cell invasion of liver 20 , cervical 21 , and breast 22 origins.…”
mentioning
confidence: 99%
“…Using a near-infrared light source, pSi has been shown to have heat generation abilities, attributed to high absorbance and large surface-to-volume ratio. [49] Future applications include the use of pSi particles to enhance radiofrequency-induced thermal ablation of cancer cells, expanding the versatility of pSi.…”
Section: Future Perspectivesmentioning
confidence: 99%